1999
DOI: 10.1068/a310477
|View full text |Cite
|
Sign up to set email alerts
|

Distance Effects in the Demand for Wildland Recreational Services: The Case of National Parks in the United States

Abstract: Distance decay in spatial demand usually is taken as axiomatic. There are, however, a number of situations in which distance decay cannot be taken for granted. In recreational pursuits, for example, spatial interaction is often marked by a confounding distance effect in which nearby and more distant destinations are equally attractive. The research reported in this paper concerns an examination of the distance effect in the spatial demand for a specific type of recreation: the use of national parks in the USA.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
60
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(61 citation statements)
references
References 38 publications
0
60
0
1
Order By: Relevance
“…results in increasing expenditures and, as a consequence, in travel cost. Also travelling farther increases the travel cost, although this is not the rule for all study cases (Hanink and White, 1999). In the Floodplain, distance and travel cost are highly correlated variables (Pearson r = 0,7; p = 0,005; n = 87), emphasizing the effect showed on Equation 1.…”
Section: Effect Of Interaction Among Significant Variables ψ (Estimatmentioning
confidence: 88%
“…results in increasing expenditures and, as a consequence, in travel cost. Also travelling farther increases the travel cost, although this is not the rule for all study cases (Hanink and White, 1999). In the Floodplain, distance and travel cost are highly correlated variables (Pearson r = 0,7; p = 0,005; n = 87), emphasizing the effect showed on Equation 1.…”
Section: Effect Of Interaction Among Significant Variables ψ (Estimatmentioning
confidence: 88%
“…Despite the fact that several studies have identified a positive influence of park age over demand (Mills & Westover, 1987;Hanink & White, 1999;Neuvonen et al, 2010), it is not certain how this variable affects demand. While the most outstanding attractions of a country are primary designated protected areas, older parks have had more time to be structured (e.g., facilities, staff, services) and develop their reputation.…”
Section: Parks Vol 212 November 2015mentioning
confidence: 99%
“…To travel a certain distance to somewhere is costly and even if the actual physical cost of travel to a location is not great, there are associated costs like uncertainty and time [24]. This can create distance decay effects as closer and better-known places are seen therefore as less costly.…”
Section: Distance Decaymentioning
confidence: 99%
“…In that case, the suggestion should be that millennials are willing to travel from further away to visit RUNP, but it is clearly seen that this is not the case. Another study also used distance decay to study national park visitors in America and worked with the theory that parks farther away are seen as less congested and therefore more desirable creating almost an opposite case to distance decay theory [24]. This study also mentioned, however, that closer parks, which could be interpreted as UNP, provide necessary green areas for more frequent, short-term visits with fewer people visiting as distance increased away from these areas [24].…”
Section: Distance Decaymentioning
confidence: 99%
See 1 more Smart Citation